IDENTIFICATION OF CACING SOIL TRANSMITTED HELMINTHES EGGS ON THE NAIL OF CLEANING OFFICER OF THE GORONTALO DISTRICT LIVING OFFICER - Yahya, Elsya Novyana (LP2M Universitas Bina Mandiri Gorontalo, 2023)
Soil Transmitted Helminthes eggs are one type of worm eggs that can cause worm infections. Some of the factors that can affect it are nail hygiene and hand washing. Based on data from the Gorontalo Provincial Health Office in 2018, it shows that the prevalence of worms in Gorontalo District is around 8.7%. The purpose of the study was to identify Soil Transmitted Helminthes eggs on the nails of the cleaning officers of the Gorontalo District Environmental Office. This research is quantitative descriptive with total sampling technique and sample size 47, with sedimentation inspection method using 0.9% NaCl solution. The data analysis technique used univariate analysis. Based on the research that has been done, it was found 3 positive samples of worm eggs on the nails of the janitor and the frequency in this study was 6.4%. This is due to the lack of personal hygiene application, such as not routinely cutting nails once a week and not using personal protective equipment, namely gloves when working with direct contact with the soil and garbage, so it is hoped that cleaning staff will routinely cut nails once a week and use gloves when work and for the next researcher to check fecal matter on the cleaners of the Gororntalo Regency Environmental Agency.